Palladium‐Catalyzed Desulfitative Arylation of 5‐Alkoxy‐3, 4‐dibromo‐2(5H)‐furanone with Sodium Arylsulfinates. Issue 6 (19th January 2015) - Shi, Jie; Tang, Xiao‐Dong; Wu, Yan‐Cheng; Li, Hua‐Nv; Song, Liu‐Juan; Wang, Zhao‐Yang
Abstract: A palladium‐catalyzed desulfitative arylation reaction of 5‐alkoxy‐3, 4‐dibromo‐2( 5H )‐furanones to provide 5‐alkoxy‐4‐aryl‐3‐bromo‐2(5 H )‐furanones is reported. This reaction has a high reaction site selectivity, which can realize arylation at the C4‐position. Various sodium arylsulfinates are well tolerated under the mild reaction conditions. The current study makes the arylation of general alkenyl halides possible by the use of cheap and easily available sodium arylsulfinates as aryl sources. Abstract : A palladium‐catalyzed desulfitative arylation reaction of 5‐alkoxy‐3, 4‐dibromo‐2(5 H )‐furanone to provide 5‐alkoxy‐4‐aryl‐3‐bromo‐2(5 H )‐furanone has been reported. Various sodium arylsulfinates as cheap and easily available aryl sources are well tolerated under the mild reaction conditions.